ANALISIS KUALITAS LAYANAN SISTEM INFORMASI AKADEMIK UNIVERSITAS ABDURRAB TERHADAP KEPUASAN PENGGUNA MENGGUNAKAN METODE SEVQUAL (Studi Kasus : Mahasiswa Universitas Abdurrab Pekanbaru) - Yuni Septiani; Edo Aribbe; Risnal Diansyah (Universitas Islam Kuantan Singingi, 2020)
Academic Information System is the name of an information system used for academic activities at Abdurrab University and also known as SIMAK. Abdurrab University has been implementing Academic Information Systems since 2016, but in the application of this system there are still some obstacles so that it will affect what is to be achieved, one of which is user satisfaction. In this study the method used is the Service Quality method with measurements based on dimensions of service quality which include Tangible, Reliability, Responsibility, Assurance and Empathy. The purpose of this study was to determine how much influence the quality of Academic Information Systems on user satisfaction using the Servqual method with the IBM SPSS Statistics 24.0 tool. This research is a quantitative research using survey method. The technique in sampling in this study is to use non-probability techniques or using the Quota Sampling Technique. In this case the formula used in sampling is the Slovin formula, so this study obtained a sample size of 96 respondents. Based on the evaluation results it can be concluded that the Empathy variable significantly influences user satisfaction by 44.8%, while simultaneously Tangible, Reliability, Responsiveness, Assurance and Empathy variables together have a significant influence on user satisfaction at the significance level α = 10% .